THE EFFECT OF CAPITAL STRUCTURE, THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE, AND AUDIT QUALITY ON THE COMPANY'S VALUE - Diah Nurdiana; Afly Yessie; Desi Sunarti (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the influence of capital structure, the implementation of good corporate governance (which is proxied through institutional ownership, managerial ownership, and independent board of commissioners), and audit quality on company value. The main problem of this study arises because of the inconsistent results of previous research on factors that affect the value of companies, especially in the property and real estate sectors in Indonesia. The research method used is quantitative with a descriptive approach. Secondary data was obtained from the annual financial statements of property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. The sampling technique used purposive sampling with the criteria of companies that reported complete financial statements during the study period. Data analysis was carried out using multiple linear regression through SPSS version 26 with classical assumption test, partial test (t), simultaneous test (F), and determination coefficient (Adjusted R²). The results of the study show that the capital structure has a significant positive effect on the value of the company; institutional ownership and an independent board of commissioners have a significant positive effect; managerial ownership has no significant effect; Meanwhile, audit quality has a positive effect on the company's value. In conclusion, the better the capital structure, corporate governance, and audit quality, the higher the value of companies in the property and real estate sectors on the IDX.Keywords: Capital Structure, Good Corporate Governance, Audit Quality, Company Value